Glycemic control, inflammation, and cognitive function in older patients with type 2 diabetes. (20th February 2015) - Akrivos, Jimmy; Ravona‐Springer, Ramit; Schmeidler, James; LeRoith, Derek; Heymann, Anthony; Preiss, Rachel; Hoffman, Hadas; Koifman, Keren; Silverman, Jeremy M.; Schnaider Beeri, Michal
<x xml:space="preserve">Abstract</x> Objective Glycated hemoglobin (HbA1c) and C‐reactive protein (CRP) have been associated with cognitive impairment independently. However, it is unclear if their combination exacerbates poor cognitive function. We assessed whether long‐term glycemic level and glycemic variability modulate the association of systemic inflammation with cognitive function, in a sample of cognitively normal older people with type 2 diabetes. Methods A retrospective cohort study of 777 randomly selected participants from 11, 000 patients in the Maccabi Healthcare Services Diabetes Registry, as part of the Israel Diabetes and Cognitive Decline study. Subjects averaged 18 (±9.4) HbA1c measures in the Maccabi Healthcare Services Registry, which were used to calculate long‐term glycemic level (HbA1c‐mean) and glycemic variability (HbA1c‐standard deviation (SD)). Linear regression models assessed the interactions of CRP, a marker of systemic inflammation, with HbA1c‐mean and HbA1c‐SD on subjects' performance in tests of Memory, Executive Functions, Attention, and Semantic Categorization. Results Quadratic interactions of CRP with HbA1c‐SD approached significance for executive functions and overall cognition. However, after Bonferroni adjustment, none of the interactions of CRP with HbA1c were statistically significant. In partial correlations according to HbA1c‐SD tertiles, CRP was weakly correlated in the middle tertile with decreased performance in the domains of semantic categorization (r = −0.166, p = 0.011), executive functions (r = −0.136, p = 0.038), and overall cognition (r = −0.157, p = 0.016). Conclusions Glycated hemoglobin does not substantially modulate the association of CRP with cognition in a sample of cognitively normal, community dwelling older people with relatively well‐managed type 2 diabetes. Copyright © 2015 John Wiley & Sons, Ltd.